FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KEPATUHAN PENGGUNAAN ALAT PELINDUNG DIRI PADA PETUGAS KESEHATAN DALAM MASA PANDEMIK COVID 19 DI RSUD BAHTERAMAS PROVINSI SULAWESI TENGGARA TAHUN 2021 - Nurdian Nurdian; Hariati Lestari; Rastika Dwi Liaran (Endemis Journal, 2022)
Coronaviruses are a large family of viruses that cause illness ranging from mild to severe symptoms. Coronaviruses are known to cause diseases that cause severe symptoms such as Middle East Respiratory Syndrome (MERS) and Severe Acute Respiratory Syndrome (SARS). This study aims to determine the factors related to compliance with the use of personal protective equipment by health workers during the COVID-19 pandemic at Bahteramas Hospital, Southeast Sulawesi province in 2021. This study used a case control design. The population in this study were health workers at Bahtermas Hospital totaling 640 health workers. The sample in this study amounted to 234 respondents consisting of 8 groups of health workers. Sampling using the Lemeshow formula. The results showed that based on the results of the chis square test, the P-value of the knowledge variable was 0.003, the Attitude variable, a P-Value of 0.01 was obtained and the PPE availability variable was a P-Value of 0.02. From the 234 research samples used, it can be concluded that the Knowledge, Attitude and availability of PPE are related to compliance with the use of PPE by health workes during the COVID-19 pandemic at Bahteramas Hospital, Southeast Sulawesi Province.